2015
DOI: 10.1264/jsme2.me15109
|View full text |Cite
|
Sign up to set email alerts
|

Community Analysis of Root- and Tuber-Associated Bacteria in Field-Grown Potato Plants Harboring Different Resistance Levels against Common Scab

Abstract: Eight genotypes of potato plants with different resistance levels against common scab were grown in a field infested with Streptomyces turgidiscabies. DNA was extracted from the roots, tubers, and rhizosphere soils of each of the eight genotypes at the flowering stage, and the quantity of S. turgidiscabies genomic DNA was assessed by real-time PCR using a TaqMan probe. The results obtained showed that the different potato genotypes had significant impacts on the population levels of S. turgidiscabies between r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 42 publications
1
21
0
Order By: Relevance
“…The overall ubiquitous presence of Arthrobacter strains could be due to their extraordinary traits such as enormous nutritional versatility, high resistance to desiccation and starvation (Hagedorn and Holt, 1975;Cacciari and Lippi, 1987) as the sampling field was characterized by high salinity and low water content. Our results are consistent with the findings of Kobayashi et al (2015), who found Arthrobacter nicotinovorans to be frequently associated with roots and tubers of different potato cultivars. Arthrobacter species are known to be involved in the biodegradation of organic matter (Cacciari and Lippi, 1987) and may produce antibiotics (Kamigiri et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overall ubiquitous presence of Arthrobacter strains could be due to their extraordinary traits such as enormous nutritional versatility, high resistance to desiccation and starvation (Hagedorn and Holt, 1975;Cacciari and Lippi, 1987) as the sampling field was characterized by high salinity and low water content. Our results are consistent with the findings of Kobayashi et al (2015), who found Arthrobacter nicotinovorans to be frequently associated with roots and tubers of different potato cultivars. Arthrobacter species are known to be involved in the biodegradation of organic matter (Cacciari and Lippi, 1987) and may produce antibiotics (Kamigiri et al, 1996).…”
Section: Discussionsupporting
confidence: 93%
“…Our results are consistent with the findings of Kobayashi et al . (), who found Arthrobacter nicotinovorans to be frequently associated with roots and tubers of different potato cultivars. Arthrobacter species are known to be involved in the biodegradation of organic matter (Cacciari and Lippi, ) and may produce antibiotics (Kamigiri et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The soil which was loosely attached to the roots was removed by gentle shaking. Tightly bound soil was considered rhizospheric and was obtained by firmly shaking the root system in a sterile plastic bag (Kobayashi et al, 2015;Tan et al, 2017b). The rhizospheric soil samples were thoroughly mixed, and randomly divided into three subsamples, as described previously (Yu et al, 2019).…”
Section: Study Site and Experimental Designmentioning
confidence: 99%
“…There is growing awareness of the potential use of rhizospheric or endophytic bacteria as biocontrol agents to enhance resistance to plant pathogens 810 , including Streptomyces scabies 11 , which causes potato scab 12 , an agricultural disease of worldwide economic importance 13 . The primary phytotoxin, thaxtomin, is a family of 5-nitrotryptophan-containing cyclic dipeptides.…”
mentioning
confidence: 99%